GRAP2: A Novel Immune-Related Prognosis Biomarker in Cervical Cancer - Shixin Lin; Jun Zhu; Xiaoling Mao; Gang Lin; Dan Yang; Yun Guan; Jun Gao (IMR Press, 2023)
Background: Immune infiltration of the tumor microenvironment offers unlimited possibilities for therapeutic strategies in cervical cancer, where GRAP2 is an adaptor protein engaged in diverse signal activations. However, uncertainty exists regarding GRAP2's prognostic significance and its relationship to immune infiltration. Methods: The data on cervical cancer cases were downloaded from The Cancer Genome Atlas (TCGA) database. The ESTIMATE computational technique was utilized to calculate the amount of immunological and stromal components, which helped us to identify the differential expression genes (DEGs). Among them, GRAP2 was considered to be related to overall survival based on a protein-protein interaction network and a univariate Cox regression analysis. Thus, based on the Gene Expression Omnibus (GEO) and TCGA databases, we evaluated GRAP2's influence on clinical prognosis. Furthermore, GRAP2 expression was analyzed by Gene Set Enrichment Analysis (GSEA). Finally, we used CIBERSORTx analysis to assess the proportion of tumor-infiltrating immune cells (TICs) and the connection between GRAP2 and the tumor immune microenvironment. Results: ESTIMATEScore was associated with cervical cancer patient's prognosis. There are 791 DEGs and 11 potential key genes were identified including GRAP2. In survival analyses with clinical information, We found that the GRAP2 high expression group exhibited a significantly longer overall survival (OS) than the low expression group and that the gene expression gradually declined as the Federation of International of Gynecologists and Obstetricians (FIGO) stage and M classification increased. GRAP2 was strongly linked with immunity and metabolism, according to GSEA. Finally, we discovered that 11 different TIC types and GRAP2 expressions were linked. Conclusions: GRAP2 may be a novel immune-related prognosis biomarker in cervical cancer.